2022
DOI: 10.1002/1878-0261.13317
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of PD‐L1 and Ki67 in circulating tumor cells of metastatic non‐small cell lung cancer patients treated with pembrolizumab

Abstract: Programmed cell death protein ligand‐1 ( PD‐L1 ) expression in non‐small cell lung cancer (NSCLC) tumors guides treatment selection. PD‐L1 expression in circulating tumor cells (CTCs) may provide further information. We have explored PD‐L1 and marker of proliferation Ki‐67 ( Ki67 ; also known as MKI67 ) in CTCs in longitudinal samples of 47 advanced NSCLC patients receiving pembrolizumab. A triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Moreover, patients with a reduction of total and PD-L1-low CTCs after the first cycle of pembrolizumab presented a longer PFS. To the contrary, PD-L1-positive patients with a Ki67 index > 30% on baseline presented shorter PFS and OS compared to those harbouring Ki67 ≤ 30% [116].…”
Section: Pd-l1 Expression In Ctcs During Treatment With Immune Checkp...mentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, patients with a reduction of total and PD-L1-low CTCs after the first cycle of pembrolizumab presented a longer PFS. To the contrary, PD-L1-positive patients with a Ki67 index > 30% on baseline presented shorter PFS and OS compared to those harbouring Ki67 ≤ 30% [116].…”
Section: Pd-l1 Expression In Ctcs During Treatment With Immune Checkp...mentioning
confidence: 81%
“…To the contrary, Kulasinghe et al reported no association between PFS and presence of PD-L1-positive CTCs in advanced NSCLC patients [91]. Spiliotaki et al explored PD-L1 and Ki-67 in CTCs of 47 advanced NSCLC patients receiving pembrolizumab [116]. Blood samples were analysed at baseline, post-first cycle, post-third, and primary resistance (PMR).…”
Section: Pd-l1 Expression In Ctcs During Treatment With Immune Checkp...mentioning
confidence: 99%
“…It is mainly located in the cell nucleus and is expressed at high levels during the S phase and M phase. [ 31 ] Ki67 expression is used to evaluate the proliferation activity and division status of tumor cells, which is valuable for assessing tumor malignancy and prognosis. [ 32 ] Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) is used to detect apoptosis in cells; this method involves the detection of repairable structure ends of DNA fragmentation during apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating tumour cells (CTCs) are a “liquid biopsy specimen” that can replace the primary tumour ( 41 ). The expression of PD-L1 in CTCs can be used to evaluate the efficacy of PD-1/PD-L1 mAbs in non-small cell lung cancer patients ( 42 , 43 ). The use of CTCs to evaluate the expression of PD-L1 in SCLC may overcome the heterogeneity of PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%